Adaptive trellis-coded modulation over predicted flat fading channels - Falahati, S.; Svensson, A.; Sternad, M.; Hong Mei (2003 IEEE 58th Vehicular Technology Conference. VTC 2003-Fall (IEEE Cat. No.03CH37484), 2003)
We consider the optimum design of an adaptive scheme based on TCM and predicted CSI for flat Rayleigh fading channels, intended for fast link adaptation. The question of how to optimally adjust the data rate to maximize the spectral efficiency, subject to a BER constraint when imperfect CSI is taken into account, is answered. An optimum solution based on the predicted SNR and the prediction error variance is derived. The performance of the adaptive TCM scheme is illustrated by utilizing seven 4-D trellis codes based on the International Telecommunications Union's ITU-T V.34 modem standard. The results indicate that the gain in spectral efficiency by adaptive TCM is about 1-2 dB compared to adaptive uncoded M-QAM, for most of average SNRs. Finally, the performance of the adaptive TCM and in particular, its loss at high SNRs compared to adaptive uncoded M-QAM, are investigated in details.